Enhanced dewaterability of waste activated sludge by a combined use of permanganate and peroxymonosulfate. Issue 47 (2nd September 2019) - Luo, Lu; Ge, Yongjian; Yuan, Shuyu; Yu, Yanghai; Shi, Zhou; Zhou, Shiqing; Deng, Jing
Abstract : Ever-increasing efforts have been made to develop rapid and practical conditioning methods of sludge dewatering. Abstract : Ever-increasing efforts have been made to develop rapid and practical conditioning methods of sludge dewatering. This study demonstrated an innovative combination of potassium permanganate (KMnO4 ) and peroxymonosulfate (PMS) for sludge dewatering. The combined use of KMnO4 and PMS (KMnO4 /PMS) showed its superiority in improving sludge dewaterability over the separate use of KMnO4 or PMS. By dosing 4 mmol g −1 VSS KMnO4 and 3 mmol g −1 VSS PMS, the dewaterability of waste activated sludge (WAS) significantly enhanced as capillary suction time (CST) decreased from 73.65 s to 24.65 s while the water content of dewatered sludge cake ( W C ) decreased from 78.96% to 70.47%. Apart from CST and W C, the KMnO4 /PMS process could also affect negative zeta potential, sludge flocs size and the concentrations of protein and polysaccharide in extracellular polymeric substances (EPS). The enhanced sludge dewaterability and changes of the physicochemical characteristics of the WAS samples during the KMnO4 /PMS process were actually ascribed to sulfate radicals (SO4 ˙ − ) and hydroxyl radicals (HO˙) in situ generated via PMS activation by manganese oxides (MnO x ) in the states of MnO2 and Mn3 O4 transferred from KMnO4 oxidation, which was verified by transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDX) techniques and radical scavenging experiments. Moreover, the Fourier transform infrared spectroscopy (FTIR) analysis further confirmed that the in situ generated SO4 ˙ − and HO˙ could improve sludge dewaterability. Thus, the KMnO4 /PMS process could be considered as a promising conditioning method of sludge dewatering.